(untitled) (University Journal of Zoology, Rajshahi University, 2010)
The repellent activity of monoterpenoids viz. eugenol, zimtaldehyde and neem oil against pulse beetle, Callosobruchus maculatus (F.) was investigated. Responses varied significantly with compound, dose and exposure time. The tested components showed highest level of repellency against C. maculatus at a dose of 1 μl. Over 80%, Class V, repellency was achieved after 5 to 60 min. treatment with the components at a dose of 1 μl. The repellent action of zimtaldehyde showed the highest repellency (87.41% at 10 min exposure) status against C. maculatus than neem oil and eugenol, while the lowest (79.46%) was recorded for eugenol at 25 min exposure level. Key words: Repellency; eugenol; zimtaldehyde; neem oil; C. maculatus DOI: 10.3329/ujzru.v28i0.5284 Univ. j. zool. Rajshahi Univ. Vol. 28, 2010 pp. 41-44